(untitled) (Web of Teachers: Inderscience Research, 2025)
In the process of globalization of the peoples of the world, educational problems are of particular importance. “Education is the main driving force of progress and an important activity leading to the achievement of the goals of sustainable development” - this definition is given by the new concept of education until 2030, adopted by international organizations and developed countries of the world. Virtual education technologies, open educational resources, educational technologies, education management systems are effectively used to provide quality education, improve education methods for assessing learning outcomes. Based on the tasks set, the technology of teaching Karakalpak literature at academic lyceums is being improved, the information of students in literature lessons based on innovative approaches is analyzed.